Sensitization Potency of Sunflower Seed Protein in a Mouse Model: Identification of 2S‐Albumins More Allergenic Than SFA‐8. Issue 18 (19th August 2021) - Achour, Jihana; Guinot, Marine; Guillon, Blanche; Kapel, Romain; Galet, Olivier; Adel‐Patient, Karine; Hazebrouck, Stéphane; Bernard, Hervé
Abstract : Scope: Food allergy to sunflower seed (SFS) protein is not frequent and only non‐specific lipid transfert protein (nsLTP) Hel a 3 is officially recognized as a food allergen. Out of the eleven seed storage 2S‐albumins (SESA) detected in SFS, only SFA‐8 allergenicity has been investigated so far. The study aimed then to evaluate SFS protein allergenicity and particularly, to compare the sensitization potency of SESA in a mouse model. Methods and Results: The most abundant SESA and nsLTP were isolated from SFS through a combination of chromatographic methods. Purified proteins were then used to measure specific IgG1 and IgE responses in BALB/c mice orally sensitized to different SFS protein isolates. The study, thus, confirmed the allergenicity of SFA‐8 and Hel a 3 but mice were also highly sensitized to other SESA such as SESA2‐1 or SESA20‐2. Furthermore, competitive inhibition of IgE‐binding revealed that SFA‐8 IgE‐reactivity was due to cross‐reactivity with other SESA. 11S‐globulins were weakly immunogenic and were rapidly degraded in an in vitro model of gastroduodenal digestion. In contrast, Hel a 3, SESA2‐1 and SFA‐8 were more resistant to proteolysis and gastroduodenal digestion did not affect their IgE‐reactivity. Conclusions: SESA2‐1 or SESA20‐2 were more potent allergens than SFA‐8 in this mouse model. Allergenicity of SESA must be now confirmed in SFS‐allergic patients. Abstract : Allergy to sunflower seed is not frequent but non‐specific lipid transfert protein Hel a 3 and 2S‐albumin SFA‐8 are already known allergens. De novo sensitization to seed storage 2S‐albumins (SESA) was compared in a mouse model. IgE‐sensitization was evidenced for various SESA but IgE‐reactivity of SFA‐8 was due to cross‐reactivity with other SESA. SESA allergenicity must be now assessed in food‐allergic patients.